2011
DOI: 10.1371/journal.pone.0014563
|View full text |Cite
|
Sign up to set email alerts
|

Bves Modulates Tight Junction Associated Signaling

Abstract: Blood vessel epicardial substance (Bves) is a transmembrane adhesion protein that regulates tight junction (TJ) formation in a variety of epithelia. The role of TJs within epithelium extends beyond the mechanical properties. They have been shown to play a direct role in regulation of RhoA and ZONAB/DbpA, a y-box transcription factor. We hypothesize that Bves can modulate RhoA activation and ZONAB/DbpA activity through its regulatory effect on TJ formation. Immortalized human corneal epithelial (HCE) cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…It is believed that ZO-1 acts as a scaVolding protein that forms a foundation for tight junction assembly (Tsukita et al 2001). Indeed, loss of ZO-1 leads to the failure of tight junction formation (Georgiadis et al 2010;Russ et al 2011). In this investigation, we observed that symplekin and ZO-1 showed almost the same immunoXuorescence staining pattern at the tight junction in 2.5-D cell cultures, while our co-immunoprecipitation results indicated that symplekin and ZO-1 form a protein-protein complex in both HT-29 and Caco-2 epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that ZO-1 acts as a scaVolding protein that forms a foundation for tight junction assembly (Tsukita et al 2001). Indeed, loss of ZO-1 leads to the failure of tight junction formation (Georgiadis et al 2010;Russ et al 2011). In this investigation, we observed that symplekin and ZO-1 showed almost the same immunoXuorescence staining pattern at the tight junction in 2.5-D cell cultures, while our co-immunoprecipitation results indicated that symplekin and ZO-1 form a protein-protein complex in both HT-29 and Caco-2 epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR, the transmembrane protein linked to cystic fibrosis, binds and stabilises ZO-1, leading to reduced ZO-1 expression in its absence and, thereby, promoting nuclear translocation of ZONAB, induction of cyclin D1 and repression of ErbB2 147 . Manipulation of other junctional transmembrane proteins, such as BVES, regulates ZONAB activation via a GEF-H1/RhoA-stimulated mechanism 140,148 . In endothelial cells of the blood-tumour-barrier, bradykinin-induced activation of nitric oxide synthesis induces increased permeability and ZONAB activation, leading to repression of claudin-5 and occludin promoters 149 .…”
Section: Signalling From Tight Junctionsmentioning
confidence: 99%
“…2) (Aijaz et al, 2005;Benais-Pont et al, 2003;Guillemot et al, 2008a). Binding to cingulin results in the inhibition of GEF-H1 and is promoted by tight junction formation that is induced by the junctional membrane protein BVES; hence, junctional GEF-H1 is thought to be inactive (Aijaz et al, 2005;Russ et al, 2011). If it is not sequestered at tight junctions, GEF-H1 promotes various RhoA-driven processes, including cell spreading and migration, cell cycle progression and gene expression (Birukova et al, 2006;Kakiashvili et al, 2009;Krendel et al, 2002;Nie et al, 2009;Terry et al, 2011;Tsapara et al, 2010).…”
Section: Rhoa and Signalling From Tight Junctionsmentioning
confidence: 99%
“…BVES forms a complex with ZO-1 and suppresses the GEF-H1-ZONAB pathway in corneal epithelial cells. It also regulates junctional integrity through aPKC, indicating that downregulation of BVES results in the modulation of several tight-junction-associated signalling pathways (Russ et al, 2010;Russ et al, 2011;Wu et al, 2012). However, the mechanism(s) underlying the tumour suppressor activity of BVES have not been identified.…”
Section: Regulation Of Cell Behaviour and Survival By Transmembrane Pmentioning
confidence: 99%